Determination of Physicochemical and Some Heavy Metal of Soil around Dana Steel Industry Limited Katsina, Katsina State, Nigeria - Abdulhamid, Y.; Abdulsalami, M.S.; Suleiman, A.B.; Matazu, I.K. (UMYU Journal of Microbiology Research, 2017)
The aim of this study was to investigate the physicochemical parameters and level of some Heavy metal concentrations in dumpsites soil around Dana steel limited dumpsite located in latitude 12º 57¹ 43¹¹N to 12º 58¹ 7¹¹N, Longitude 7º 37¹11¹¹E to 7º 37¹ 16¹¹E and altitude 522.5m to 616.6m in Katsina state of Nigeria were investigated in this research. Soil samples were collected from the dumpsite and control site at depths ranges 0- <10cm, 10- <20cm, 20-